2020
DOI: 10.3389/fmed.2020.00214
|View full text |Cite
|
Sign up to set email alerts
|

ADAM9 Mediates Triple-Negative Breast Cancer Progression via AKT/NF-κB Pathway

Abstract: Upregulation of a disintegrin and metalloprotease 9 (ADAM9) is correlated with progression of cancers, such as prostate, bladder, and pancreatic cancers. However, its role in triple-negative breast cancer (TNBC) is still unclear. Our study aimed to investigate whether ADAM9 is upregulated and promoted the aggressiveness in TNBC. Breast cancer cell lines and patient specimens were used to evaluate the ADAM9 expression by western blotting and immunohistochemistry staining, respectively. Compared with the non-TNB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…A previous study has associated ADAM9 function in Akt regulation with EGFR activation ( 42 ). However, HCT116 cells contain a constitutively active PI3K mutation ( Table S1 ), rendering Akt activity in these cells insensitive to growth factor stimulation ( 43 ), and a recent report shows that ADAM9 activates Akt independently of EGFR ( 44 ). We have shown that KD of ADAM9 results in increased levels of intact ephrin-B1 and active EphB3 receptor ( Figs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study has associated ADAM9 function in Akt regulation with EGFR activation ( 42 ). However, HCT116 cells contain a constitutively active PI3K mutation ( Table S1 ), rendering Akt activity in these cells insensitive to growth factor stimulation ( 43 ), and a recent report shows that ADAM9 activates Akt independently of EGFR ( 44 ). We have shown that KD of ADAM9 results in increased levels of intact ephrin-B1 and active EphB3 receptor ( Figs.…”
Section: Resultsmentioning
confidence: 99%
“…We found that ADAM9 mRNA is also elevated in CRC tissues and identified Akt and downstream Wnt and mTOR signaling as the main targets for ADAM9 in CRC cells. Two published works have linked ADAM9 to Akt activity in esophageal squamous cell carcinoma and triple-negative breast cancer, respectively ( 42 , 44 ). Together with our results, these suggest that ADAM9 is a key Akt regulator in various tumors.…”
Section: Discussionmentioning
confidence: 99%
“…• siRNA targets: ADAM9 [87]; AKT2 [88]; EGFR [89]; CD44 [90]; BRD4 [91]; IKBKE [61]; ICAM1 [92]; TTK, CDC20 [93]; POLR2A [94]; survivin [64]; MTOR (mTORC2) [95]; oncogenic lncRNAs TMPO-AS1 [96]/DANCR [97]; CD44 [98]; EIF4E (eIF4E) [99]; ZRANB1 [100] • shRNA targets: EZH2 [100]; LGALS1 (galectin-1) [101]; USP39 [102] There has been significant progress in developing RNA-based therapies for a wide variety of diseases, although primarily preclinically for TNBC to date. Although there are several promising early-stage studies for TNBC using RNAi and RNA immunotherapy as was described in Section 1.3, and combinatorial RNA-based therapies, described in Section 1.4, it is important to recognize that there is still a significant amount of work until these therapeutic agents/strategies will advance to clinical evaluation.…”
Section: Therapeutic Applications Of Rna-based Methods For Treatment Of Tnbc 21 Pre-clinical Progress Of Rna-based Therapiesmentioning
confidence: 99%
“…Liu et al also proved that the combination of Fei-Liu-Ping ointment with celecoxib inhibits the tumor inflammatory microenvironment in an LLC xenograft model [ 78 ]. Disintegrin and a metalloproteinase (ADAM9), a type I transmembrane protein, are overexpressed in various cancers, including lung cancer [ 135 , 136 , 137 ]. Lin et al proved that a secreted form of ADAM9 promotes cancer invasion through tumor-stromal interactions [ 137 ].…”
Section: Combination Of Natural Products and Anticancer Drugsmentioning
confidence: 99%